Targeting connexin 43 protects against the progression of experimental chronic kidney disease in mice - Abed, Ahmed; Toubas, Julie; Kavvadas, Panagiotis; Authier, Florence; Cathelin, Dominique; Alfieri, Carlo; Boffa, Jean-Jacques; Dussaule, Jean-Claude; Chatziantoniou, Christos; Chadjichristos, Christos E. (Kidney international, 2014)
Excessive recruitment of monocytes and progression of fibrosis are hallmarks of chronic kidney disease (CKD). Recently we reported that the expression of connexin 43 (Cx43) was upregulated in the kidney during experimental nephropathy. To investigate the role of Cx43 in the progression of CKD, we interbred RenTg mice, a genetic model of hypertension-induced CKD, with Cx43+/- mice. The renal cortex of 5-month-old RenTgCx43+/- mice showed a marked decrease of cell adhesion markers leading to reduced monocyte infiltration and interstitial renal fibrosis compared with their littermates. In addition, functional and histological parameters such as albuminuria and glomerulosclerosis were ameliorated in RenTgCx43+/- mice. Interestingly, treatment with Cx43 antisense produced remarkable improvement of renal function and structure in 1-year-old RenTg mice. Similar results were found in Cx43+/- or wild-type mice treated with Cx43 antisense after obstructive nephropathy. Furthermore, in these mice, Cx43 antisense attenuated E-cadherin downregulation and phosphorylation of the transcription factor Sp1 by the ERK pathway resulting in decreased transcription of type I collagen gene. Interestingly, Cx43-specific blocking peptide inhibited monocyte adhesion in activated endothelium and profibrotic pathways in tubular cells. Cx43 was highly increased in biopsies of patients with CKD. Thus, Cx43 may represent a new therapeutic target against the progression of CKD.